Bacterial community structure and metabolites after ensiling paper mulberry mixed with corn or wheat straw - Huang, Rongzheng; Cai, Bingxin; Chen, Yongcheng; Zheng, Xiaokai; Yang, Jianqi; Ma, Chunhui; Wang, Xuzhe; Zhang, Fanfan (Frontiers in Sustainable Food Systems, 2024)
Background In this study, we aimed to address the low utilization of straw and poor fermentation quality of paper mulberry silage (under natural fermentation conditions). Straw was combined with paper mulberry for ensiling, and the fermentation characteristics, bacterial community, and metabolite composition of the mixed straw and paper mulberry silage were investigated. Four treatment groups were established: corn-straw treatment 2 (3:7 ratio of corn straw to paper mulberry), corn-straw treatment 3 (5:5 ratio of corn straw to paper mulberry), wheat-straw treatment 2 (3:7 ratio of wheat straw to paper mulberry), wheat-straw treatment 3 (5:5 ratio of wheat straw to paper mulberry), and a control group (ensiling of paper mulberry alone). Results The control group demonstrated the highest pH and ammonia (AN) and acetic acid (AA) content compared with all the treatment groups. Corn-straw treatment 2 had the highest lactic acid content (54.70 g/kg dry weight) compared with the control and other treatment groups. The relative abundance of Enterobacter (7.085%) was the lowest in the control than in the other treatment groups (p < 0.05). The relative abundance of Enterococcus was higher in both the control and wheat-straw treatment 2 (22.03% and 21.29%, respectively) than in other treatment groups. The relative abundance of Lactococcus was highest in wheat-straw treatment 3 (15.83%) compared with the control and other treatment groups. Corn-straw treatments 2 and 3 demonstrated the same metabolite composition but were clearly different from the wheat-straw treatment 2, wheat-straw treatment 3, and the control. Diacetoxyscirpenol (DAS) belongs to the Fusarium metabolite type A trichothecenes, which were not detected in corn or wheat silage. DAS was downregulated in the wheat-straw treatment 3 and both corn-straw treatments compared with the control, which indicates that the addition of straw decreased mycotoxin production. Lactococcus was significantly and positively correlated with gluconic acid content (R2 = 0.5166). Conclusion Our results suggest that straw treatment can improve the nutritional value of paper mulberry silage by decreasing mycotoxin production, pH value, and AN content and increasing lactic acid production.